Social and Cultural Diversity An Anthropological reading in the Cultural and class Hierarchy in Communities: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Yousif Enad Zamil, Prof. Dr.; Prof. Dr. Jameel Mohsin Mansour, Prof. Dr. (lark, 2022)
The concept of culture is considered inherent to the social sciences, especially in its Anthropological depth. It is necessary for Human Unity through diversity that is different than thinking relying on Biology. This concept seems the most compelling answers about the difference between Nations. If culture is not the feeding source and the legacy from one generation to another, this will not be considered as a historic result, but it is a construction that will be registered in History's record. From the other hand and precisely, it can be listed in among the social groups history that assemble a social and cultural Hierarchy considering to the stratification that already existed in modern and ancient communities. In order to analyze a certain cultural system, we have to analyze the social historic status of the communities that resulted from this system. So, the concept of culture goes with everything that is humanitarian, and this concept afford the possibility of understanding the Human unity in his life, believes and culture diversity, and the unity of diversity. The concept of cultutre is considered as a proper tool to stop all the explanations of nature for human behavior. The human culture can be interpreted through the culture, because culture domain on the roles gender division and tasks in the Human communities. As a result of the mentioned above, we can remark diversity from one community to another, instead the gradual of different social communities can be seen in different time and place considering the a social and cultural hierarchy diversity.( Cultural and Social diversity, Cultural gradation, Class)
Keywords: Cultural and Social diversity , Cultural gradathon , Class..